1976
DOI: 10.1149/1.2132653
|View full text |Cite
|
Sign up to set email alerts
|

Dental Amalgam Stabilization by Selective Interfacial Amalgamation

Abstract: The purpose of this investigation was to explore the feasibility of enhancing the electrochemical stability of dental amalgam restorations by a process of “selective interfacial amalgamation.” If dental amalgam restorations can be selectively alloyed at the tooth‐amalgam interface, to a minor thickness as compared with the dimensions of the bulk amalgam, so as to present a more electrochemically stable phase than γ2 to the oral environment, corrosion will be reduced and desirable qualities of existing amalga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…20,21 A further attempt to improve the interface between amalgam and tooth by bonding was made by Zardiackas in 1976. 22 He developed the so-called 'selective interfacial amalgamation' liner by combining components of polycarboxylate cement with amalgam alloy particles. This liner was tested in tensile adhesion and microleakage tests and found to give tensile bond strengths of around 3.5 MPa, with shear punch bond strengths up to 15 MPa, 23 and to inhibit microleakage as well.…”
Section: Primersmentioning
confidence: 99%
“…20,21 A further attempt to improve the interface between amalgam and tooth by bonding was made by Zardiackas in 1976. 22 He developed the so-called 'selective interfacial amalgamation' liner by combining components of polycarboxylate cement with amalgam alloy particles. This liner was tested in tensile adhesion and microleakage tests and found to give tensile bond strengths of around 3.5 MPa, with shear punch bond strengths up to 15 MPa, 23 and to inhibit microleakage as well.…”
Section: Primersmentioning
confidence: 99%
“…To overcome the disadvantages of amalgam and reap the benefits of bonding composite, the concept of bonded amalgam was introduced in 1976 by Zardiackas. [3] This technique involves adhesive systems that reliably bond to enamel and dentin. Several studies have concluded that bonded amalgam restorations result in reduced marginal leakage at the tooth-amalgam interface compared to conventional amalgam restorations.…”
Section: Introductionmentioning
confidence: 99%